Vegetable Growers' Water Use and Conservation Practices in Miami-Dade County - Rafael Muñoz-Carpena; Jonathan H. Crane; Glenn D. Israel; Teresa Olczyk (EDIS)
This fact sheet reports water conservation trends for vegetable producers based on an extensive survey carried out in Miami-Dade County. This document is Fact Sheet ABE346, one of a series of Agricultural and Biological Engineering Department, Florida Cooperative Exension Service, Institute of Food and Agricultural Sciences, University of Florida. Published December 2003.